The Diverse Effects of Government Sponsored Health Insurance and the Role of Public Hospitals in Kerala - Philip, Cyril; Devika, P. (Social Change, 2024)
The Kerala model of development, founded on'good health at low cost' in the 1970s, was seriously threatened by economic, social, demographic, and epidemiological transitions in Kerala, leading to'poor health at exorbitant cost' by the early 2000s. To tack
Keywords: Government Sponsored Health Insurance; Healthcare Costs; Public Hospitals; Kerala